Uncovering Buried Structure and Interfaces in Molecular Photovoltaics. (22nd August 2014) - Gilchrist, James B.; Basey‐Fisher, Toby. H.; Chang, Sharon C'E.; Scheltens, Frank; McComb, David W.; Heutz, Sandrine
<x xml:space="preserve">Abstract</x> The processes that generate current in organic photovoltaics are highly dependent on the micro‐ and nano‐structure in the semiconductor layers, especially at the donor‐acceptor interface. Elucidating film properties throughout the thickness of the devices is therefore key to their further development. Here, a methodology is developed to gain unprecedented insights into the structure and composition of the molecular layers within the depth of device structure using high resolution transmission electron microscopy (HRTEM). The technique was applied to three archetypical solar cell configurations consisting of copper phthalocyanine (CuPc) and C60, which have been cross‐sectioned using a focused ion beam method optimized to minimize sample damage. The HRTEM images exhibit lattice fringes in both CuPc and C60, confirming the crystallinity and texture of both materials, and offering novel insight into the growth of C60 onto molecular materials. The donor‐acceptor interface morphology is further studied using scanning transmission electron microscopy (STEM) in combination with energy dispersive X‐ray (EDX) spectroscopy, extending the scope of our methodology to amorphous heterostructures.